2019
DOI: 10.18805/ag.d-4932
|View full text |Cite
|
Sign up to set email alerts
|

Response of Soybean [Glycine max (L.)Merrill] to Irrigation at Different Growth Stages

Abstract: A field experiment was carried out in rainy seasons of 2009, 2010 and 2011 to study the effect of irrigation schedules on yield, water use efficiency and other traits in soybean. Seven irrigation schedules consisted of irrigations at seedling stage (15-20 days after sowing), flower initiation stage, seed filling stage (20 days after flower initiation) and four different combinations of these 3 stages. Irrigation at flower initiation + seed filling stages produced the highest seed yield (3221 kg/ha). Maximum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…For soybean, Baghel et al [82] showed that water stress at the flowering stage severely decreased all of the above parameters in soybean. Jaybhay et al [83] reported that irrigation to the soybean crop at flower initiation and seed filling stages helps to obtain the optimum WUE. Currently, many studies only focused on the critical growth stages, not quantitative analysis on the stress factors of WUE-SF for soybean.…”
Section: Wue-sf Under Water Stresses For Different Eroded Soilsmentioning
confidence: 99%
“…For soybean, Baghel et al [82] showed that water stress at the flowering stage severely decreased all of the above parameters in soybean. Jaybhay et al [83] reported that irrigation to the soybean crop at flower initiation and seed filling stages helps to obtain the optimum WUE. Currently, many studies only focused on the critical growth stages, not quantitative analysis on the stress factors of WUE-SF for soybean.…”
Section: Wue-sf Under Water Stresses For Different Eroded Soilsmentioning
confidence: 99%
“…Organic nutrient management ensued significantly higher number of pods/plant and seed yield than inorganic and integrated practices (Shirale et al, 2017). Crop with organic sources showed about 18.5% increase in yield over inorganically managed crop, which might be owing to application of organic sources of nutrients (Jaybhay et al, 2015).…”
Section: Effect Of Nutrient Management On Yield Attributes and Yield ...mentioning
confidence: 93%
“…is an important oilseed crop and finds an important place in crop rotations of Central India. Soybean fixes atmospheric nitrogen, thus enriches the soil and partially fulfil the nitrogen requirement of succeeding crops for higher productivity (Jaybhay et al, 2015). Similarly, linseed (Linum usitatissimum L.) occupies the second position among the winter (rabi) season oilseed crops next to rapeseed-mustard.…”
mentioning
confidence: 99%
“…Baghel et al (2018) showed that water stress at the flowering stage severely decreased all of the above parameters in soybean. Jaybhay et al (2019) reported that irrigation of soybean crop at flower initiation and seed filling stages helped to obtain optimal WUE. This study proves that the AquaCrop model moderately predicts soybean growth and yield using mulch in a tropical environment.…”
Section: Effectiveness Of Alternative Irrigationmentioning
confidence: 99%